Radar reflection of cloud and weather precipitation at the various waves - Mikhail Rubenovich Vatiashvili (Наука. Инновации. Технологии)
The article gives a brief analysis of technical features of automated meteorological radars by means of which radar constant data (Сλi) for three channels - λ1 = 3,2 cm, λ2 = 10,3 cm, λ3 = 5,6 cm, were calculated according to the instrumentation measurements. Taking into account the wave-length, by means of Сλi the specific particle backscattering area of cloud and weather precipitation (later CWP) ηλ, сm-1 was calculated, and without taking into account the wave-length - radar reflection of CWP (Z, mm6 ∙ m-3) at different units. Tables connecting ηλi and Z that may be used for converting the value of ηλ into the value of Z and vice-versa have been compiled. The obtained results can be applied for planning and implementing projects on affecting hailing and man-made increasing of cloud precipitation; perfecting the present and developing the new ones: radar criteria of hail risk of target objects and cloud suitability for artificial precipitation provoking; evaluation methods of physical and economic efficiency when executing anti-hail works as well as works on man-made precipitation increasing.